The Effect of Cost, Brainware and Software on Computer-Based Information Systems - Dohona, Novemi; Ali, Hapzi (Siber International Journal of Education Technology (SIJET), 2024)
The Effect of Cost, Braindware and Software on Computer-Based Information Systems is a scientific article of literature study within the scope of CBIS. The purpose of this article is to build a hypothesis of the influence between variables that will be used in future research. The object of research is in online libraries, Google Scholar, Mendeley and other academic online media. The research method with the library research is sourced from e- books and open access e-journals. Qualitative descriptive analysis. The results of this article: 1) cost affects Computer-Based Information Systems;2) Braindware affects Computer- Based Information Systems; and 3) Software affects Computer-Based Information Systems.